2010
DOI: 10.1086/656316
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Antiviral Treatment in Human Influenza A(H5N1) Infections: Analysis of a Global Patient Registry

Abstract: H5N1 causes high mortality, especially when untreated. Oseltamivir significantly reduces mortality when started up to 6-8 days after symptom onset and appears to benefit all age groups. Prompt diagnosis and early therapeutic intervention should be considered for H5N1 disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
100
2
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(107 citation statements)
references
References 25 publications
3
100
2
2
Order By: Relevance
“…Our other findings that NAI treatment at any time versus no NAI, and later NAI treatment compared with no NAI, universally increased the risks of IRP, contrast sharply with previous observational data on hospitalised influenza patients which found that NAI treatment (irrespective of timing) and later antiviral therapy (initiated >48 hours after illness onset) may improve a range of clinical outcomes 19, 23, 24, 25, 26, 27, 28. Essentially similar observations were made for ‘any pneumonia’.…”
Section: Discussioncontrasting
confidence: 99%
“…Our other findings that NAI treatment at any time versus no NAI, and later NAI treatment compared with no NAI, universally increased the risks of IRP, contrast sharply with previous observational data on hospitalised influenza patients which found that NAI treatment (irrespective of timing) and later antiviral therapy (initiated >48 hours after illness onset) may improve a range of clinical outcomes 19, 23, 24, 25, 26, 27, 28. Essentially similar observations were made for ‘any pneumonia’.…”
Section: Discussioncontrasting
confidence: 99%
“…Analysis suggested that the use of oseltamivir was associated with a significant reduction in mortality, benefit was greatest when treatment was started within the first two days following symptom onset, but some benefit persisted for up to six to eight days following symptom onset. 52 The standard dosing and duration of oseltamivir is 75 mg twice daily for five days, but a higher dose of 150 mg twice daily and a longer duration of 10 days may be considered, especially in patients with pneumonia or clinical progression. 53 The World Health Organization recommends that household contacts of patients with H5N1 avian influenza should receive post-exposure prophylaxis with 75 mg of oseltamivir once daily for seven to ten days.…”
Section: Treatmentmentioning
confidence: 99%
“…9 Earlier WHO guidelines also recommend oseltamivir as the primary antiviral agent for treatment of confirmed and suspected cases of avian H5N1 influenza infection in humans; treatment should begin as soon as possible, but can be beneficial even in patients who present later in the disease course. 11,12 Again, consideration should be given to higher doses and/or longer treatment duration, depending on the clinical course of disease. …”
mentioning
confidence: 99%